Understanding counterfactuals, understanding causation : issues in philosophy and psychology - Hoerl, Christoph; McCormack, Teresa; Beck, Sarah (Oxford : Oxford University Press, 2011)
How are causal judgements such as 'the ice on the road caused the traffic accident' connected with judgements such as 'if there had not been any ice on the road, the traffic accident would not have happened'? This book looks at this question by uniting psychological and philosophical approaches to causation and counterfactuals.
Includes bibliographical references and index.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Keywords: Causation; Counterfactuals (Logic)